Antiamnesic and Neurotrophic Effects of Parkia biglobosa (Jacq.) R. Br (Fabaceae) Aqueous Extract on In Vivo and In Vitro Models of Excitotoxicity - Antoine Kavaye Kandeda; Liliane Yimta Foutse; Corneille Tongoue; Jean Philippe Djientcheu; Théophile Dimo (Behavioural Neurology)
Amnesia is a memory disorder marked by the inability to recall or acquire information. Hence, drugs that also target the neurogenesis process constitute a hope to discover a cure against memory disorders. This study is aimed at evaluating the antiamnesic and neurotrophic effects of the aqueous extract of Parkia biglobosa (P. biglobosa) on in vivo and in vitro models of excitotoxicity. For the in vivo study, 42 adult male rats were divided into six groups of seven rats each and treated daily for 30 days as follows: normal control group (distilled water, 10 mL/kg, po), negative control group (distilled water, 10 mL/kg, po), positive control group (piracetam, 200 mg/kg, po), and 03 test groups (extract, 44, 88, and 176 mg/kg, po). Scopolamine (0.5 mg/kg, ip) was administered once daily, 45 min after these treatments, for 14 days, except in the normal control group. The animals were then subjected to short-term memory (new object recognition and T-maze) and long-term memory (radial arm maze) tests for 15 following days. Animals were then euthanized, and biochemical analyses (neurotransmitters, oxidative status, and neuroinflammation) were performed in the prefrontal cortex, hippocampus, and serum. Histological analysis of these organs was also carried out. In the in vitro study, the effect of the extract (5, 10, 19, 40, 77, 153, 306, 615, 1225, and 2450 μg/mL) was assessed on the viability of primary cortical neurons exposed to L-glutamate (0.1 mg/mL). Scopolamine induced memory impairment and increased oxidative stress, neuroinflammation, and neuronal loss. P. biglobosa extract (44 mg/kg) reduced (p<0.001) short- and long-term memory deficit. It also increased (p<0.01) the concentration of acetylcholine, reduced (p<0.001) that of malondialdehyde, and limited (p<0.001) neuroinflammation and neuronal loss (p<0.001). In addition, the extract (2450 μg/mL) increased (p<0.001) the percentage of viable cells. These results suggest that the extract has effects on amnesia and neurogenesis. These effects seem to be mediated by antioxidant and anti-inflammatory modulations.